Analysis of multidrug resistance in skin lesion of inpatients and the trend of changes in a tertiary specialized hospital - Yuyang TIAN; Hui QIU; Jiao LIU (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To reveal the prevailing scenarios of cutaneous infections and multi-drug resistance of skin lesions, and nosocomial infections among inpatients in dermatology hospital. Methods Clinical data, including pathogens from skin lesions, were collected from inpatients at Dermatology Hospital of Southern Medical University between October 2019 and September 2022. The analyses included multi-drug-resistant organism (MDRO), extensively drug-resistant organisms, and the annual variations and resistance profiles of the top five pathogens. Results Over the three years, 3 331 pathogen strains were cultured from skin lesions, predominantly Gram-positive bacteria (77.72%), Gram-negative bacteria (17.35%) and fungi (4.92%). Eczematous dermatoses exhibited the highest incidence among positive cultures of skin lesions (27.32%). The top 5 pathogens were Staphylococcus aureus, Coagulase-negative staphylococci, Pseudomonas aeruginosa, Candida albicans and Klebsiella pneumoniae. The proportions of Staphylococcus aureus and Coagulase-negative staphylococci tended to be increased annually (P<0.05). However, multi-drug-resistant Staphylococcus aureus infections and methicillin-esistant Staphylococcus aureus (MRSA) tended to be decreased (P<0.05). The overall MDRO detection rate was 45.39%, with a hospital infection rate of 0.67%. The rate of MDRO in nosocomial infections declined annually (χ2=26.26, P<0.05). Conclusions Gram-positive bacteria such as staphylococci are the common pathogens in cutaneous lesion infections, suggesting that the first choice of antibiotics should be those targeting these strains. Declines in MDRO and nosocomial infections of MRSA indicate effective control of infections in the dermatology hospital. However, the increasing prevalence and resistance in coagulase-negative staphylococci underscore the need for heightened management of these infections.